Speedy Trial in Election Crimes in Indonesia: Between Judicial Efficiency and Evidentiary Integrity - Riezka Eka Mayasari; La Ode Awal Sakti; Siti Hudzaifah Miftahul Jannah; Yahyanto; Eduardo Andres Cellis (Universitas Negeri Semarang, 2025)
Speedy trials in regional election criminal cases are essential for maintaining democratic integrity, but they raise concerns about balancing efficiency with substantive justice. This study examines the implications of implementing speedy trial principles on evidence quality, access to justice, human rights protection, and judicial system integrity through normative legal analysis of primary sources. The research reveals that accelerated judicial processes create tensions between procedural speed and thoroughness, potentially compromising the examination of evidence, disadvantaging resource-limited defendants, and risking due process violations. The findings demonstrate that expedited timelines may undermine comprehensive legal reasoning in judicial decisions. A balanced framework is essential to achieve both procedural efficiency and substantive justice in electoral criminal proceedings.